Проблеми цукрознижувальної терапії за цукрового діабету 2-го типу: уроки «мегатрайлів» - Смирнов, І. І. (Clinical Endocrinology and Endocrine Surgery, 2010)
Results of randomized multicentral and long-term clinical trials devoted to the role of rigorous glycemic control in occurence and progression of micro- and macrovascular complicatoins of diabetes mellitus are analized. Euglycemia as therapeutic goal is not only desirable but also necessary. However minimization of hypoglycemic risk must be key aspect of planning treatment for every particular patient. All risk factors of cardiovascular events should be taken into consideration during implementation of therapeutic complex.